2018
DOI: 10.17219/acem/85039
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanical properties in patients with Hashimoto’s thyroiditis

Abstract: Background. Hashimoto's thyroiditis (HT) is an autoimmune endocrine disorder that results from a dysregulation of the immune system leading to an immune attack on the thyroid gland. It has potential effects on different organs and tissues. Objectives. The aim of the study was to investigate the effect of HT on corneal biomechanical properties using the ocular response analyzer (ORA). Material and methods. A total of 48 patients with HT and 49 healthy subjects were enrolled in the study. The mean age of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Previous studies mostly analysed corneal thickness in patients with TED [ 15 , 16 ] and hypothyroidism [ 7 , 17 , 18 , 19 , 20 , 21 ]. In a study that included 27 individuals with TED and 30 healthy individuals, Karabulut et al did not observe a significant difference in central corneal thickness between patients with TED and healthy individuals (with Goldmann-correlated intraocular pressure (IOPg) and corneal-compensated IOP (IOPcc) being significantly increased and corneal hysteresis (CH) being significantly decreased in patients with TED) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies mostly analysed corneal thickness in patients with TED [ 15 , 16 ] and hypothyroidism [ 7 , 17 , 18 , 19 , 20 , 21 ]. In a study that included 27 individuals with TED and 30 healthy individuals, Karabulut et al did not observe a significant difference in central corneal thickness between patients with TED and healthy individuals (with Goldmann-correlated intraocular pressure (IOPg) and corneal-compensated IOP (IOPcc) being significantly increased and corneal hysteresis (CH) being significantly decreased in patients with TED) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study that included 40 patients with euthyroid Hashimoto’s thyroiditis (HT) and 48 healthy controls found no difference in central corneal thickness, retinal thickness, and IOP between these two groups, while the levels of TPOAb negatively correlated with the retinal thickness [ 25 ]. Additionally, a study that included 48 patients with HT and 49 healthy controls did not observe a significant difference in central corneal thickness between these two groups, while IOPcc was significantly higher in the HT group [ 17 ]. However, Bassiouny et al concluded that thyroid gland dysfunction contributes to the development of corneal tomographic changes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kirgiz et al beobachteten in einer Kohorte mit Hashimoto-Thyreoiditis eine signifikant reduzierte Hornhauthysterese und einen erhöhten kornealen kompensierten IOD im Vergleich zur Kontrollgruppe. Die Verringerung der Hornhauthysterese erzeugt Druck auf den Sehnerv, was zu Komplikationen wie dem Glaukom führt [106].…”
Section: Autoimmunerkrankungen Und Ihre Auswirkungen Auf Das Augeunclassified
“…Kirgiz et al observed a Hashimoto's thyroiditis cohort to have significantly reduced corneal hysteresis and elevated corneal compensated IOP when compared to the control group. Reduction in corneal hysteresis generates pressure on the optic nerve, resulting in complications such as glaucoma (106).…”
Section: Hashimoto's Thyroiditismentioning
confidence: 99%